Teknologi pengolahan air gambut menjadi air bersih dengan sistem koagulan dan filtrasi di Desa Buluh Cina, Kecamatan Siak Hulu, Kampar - Juandi Juandi M; Usman Malik; Salomo Salomo; Antonius Surbakti (Unri Conference Series: Community Engagement, 2019)
The abundant peat water in Buluh Cina Village, Siak Hulu Subdistrict, Kampar is a natural potential that can be used for cooking and bathing purposes by processing peat water into clean water that is suitable for consumption. The purpose of this service activity is to treat peat water into clean water. The method used in this service activity is using coagulant and filtration technology. The optimal filtration and coagulant media used for peat water treatment consists of biosand filters with two media namely pumice and quartz sand. The dedication results reduce turbidity and color of peat water and reduce organic content, so that peat water is processed into clean drinking water. The lowest pH value before filtering is equal to 5.93 and the highest pH is found before filtering which is 6.23. This means that before filtering peat water is weak acidic. The lowest sample results after filtration with a slow sand filter that is equal to 6.42 and the highest pH after filtration of 7.5, which means that water is weakly basic. A good pH limit for water is 6.5 to 8.5 so this service proves that slow sand filters are considered effective enough to optimize water pH. Total dissolved solids (TDS) is one of the parameters for determining water quality, TDS shows the amount of solute solids in water. The result of peat water TDS is that the lowest TDS value before filtration is 46 mg / L and the highest TDS is found before filtering which is 49 mg/L. The lowest sample results after filtration with slow sand filter is 49 mg / L and the highest TDS after filtering is 83 mg/L.